The complete mitochondrial genome of the Gymnocypris selincuoensis (Cypriniformes: Cyprinidae) - Zhou, Jianshe (Mitochondrial DNA B Resour, 2017)
The complete mitochondrial DNA sequence of Gymnocypris selincuoensis was determined and analyzed. This mitochondrial genome was 16,728bp in length and consisted of 37genes in the typical vertebrate mitochondrial gene arrangement. Phylogenetic analysis showed that G. selincuoensis is more closely related to G. namensis than to other species.